2009
DOI: 10.1186/1757-4749-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Blood profile holds clues to role of infection in a premonitory state for idiopathic parkinsonism and of gastrointestinal infection in established disease

Abstract: The two-stage neuroinflammatory process, containment and progression, proposed to underlie neurodegeneration may predicate on systemic inflammation arising from the gastrointestinal tract. Helicobacter infection has been described as one switch in the pathogenic-circuitry of idiopathic parkinsonism (IP): eradication modifies disease progression and marked deterioration accompanies eradication-failure. Moreover, serum Helicobacter-antibody-profile predicts presence, severity and progression of IP. Slow gastroin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…Due to the chronic inflammatory nature of the H. pylori infection, it has been associated with some neurological conditions, including, Alzheimer's (Kountouras et al 2009) and Parkinson's (Charlett et al 2009) diseases, and ischemic heart disease (Longo-Mbenza 2009; Izadi et al 2012); however, currently there is insufficient data to prove a causal role for H. pylori in the pathophysiology of these diseases. Of interest however is a recent report, based on multiple logistic regression analysis, that showed that seropositivity to H. cinaedi, but not to H. pylori or Chlamydia pneumoniae, was an independent risk factor for atrial arrhythmia .…”
Section: Disease Association In Humansmentioning
confidence: 99%
“…Due to the chronic inflammatory nature of the H. pylori infection, it has been associated with some neurological conditions, including, Alzheimer's (Kountouras et al 2009) and Parkinson's (Charlett et al 2009) diseases, and ischemic heart disease (Longo-Mbenza 2009; Izadi et al 2012); however, currently there is insufficient data to prove a causal role for H. pylori in the pathophysiology of these diseases. Of interest however is a recent report, based on multiple logistic regression analysis, that showed that seropositivity to H. cinaedi, but not to H. pylori or Chlamydia pneumoniae, was an independent risk factor for atrial arrhythmia .…”
Section: Disease Association In Humansmentioning
confidence: 99%
“…Serum vitamin B 12 explained only 12% of the variance in homocysteine in IP, serum folate not contributing further [2] . Homocysteine was not related to Helicobacter infection: gastric atrophy is uncommon in IP.…”
Section: A Potential Biomarker Of Small Intestinal Bacterial Overgrowthmentioning
confidence: 99%
“…Small intestinal bacterial overgrowth was found in two thirds of a group of probands and their spouses, the hydrogen breath test status being irrespective of the subject group [2] . Clouds of lysosomes are seen in duodenal enterocytes in relation to luminal bacteria [unpubl.…”
Section: Time Sequence In Response To Interventionmentioning
confidence: 99%
See 2 more Smart Citations